2019
DOI: 10.1515/chem-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high surface area mesoporous silica SBA-15 by adjusting hydrothermal treatment time and the amount of polyvinyl alcohol

Abstract: The high surface area of mesoporous silica SBA-15 has been synthesized successfully by hydrothermal treatment with direct addition of PVA, triblock copolymer (P123) as a direct structure agent and tetraethyl orthosilicate (TEOS) as a precursor. The mesoporous silica SBA-15 have been characterized with nitrogen physisorption, scanning electron microscopy, Fourier transformed infrared spectroscopy, and x-ray diffraction. Measurement of nitrogen sorption indicated that with the addition of PVA, the surface area i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…This suggests that the modified AT is a workable process for ensuring reconfigurable surface anisotropy on the nanobeads in a single-pass configuration without using expensive crystal substrates and high vacuum conditions. X-ray diffraction (XRD) showed the coexistence of the characteristic bands for MnFe 2 O 4 , and amorphous CaCO 3 (or SiO 2 ) (Figure S6A), , presenting the growth of MnFe 2 O 4 on the nanobeads during AT. The oxidized surface states of Mn ( 2p ) and Fe ( 2p ) compared to those of the zerovalent counterparts for Mn–Fe SiO 2 (AT) with O ( 1s ) spectrum in the core level X-ray photoelectron spectra (XPS) further supported the growth of MnFe 2 O 4 (Figure S6B–D).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the modified AT is a workable process for ensuring reconfigurable surface anisotropy on the nanobeads in a single-pass configuration without using expensive crystal substrates and high vacuum conditions. X-ray diffraction (XRD) showed the coexistence of the characteristic bands for MnFe 2 O 4 , and amorphous CaCO 3 (or SiO 2 ) (Figure S6A), , presenting the growth of MnFe 2 O 4 on the nanobeads during AT. The oxidized surface states of Mn ( 2p ) and Fe ( 2p ) compared to those of the zerovalent counterparts for Mn–Fe SiO 2 (AT) with O ( 1s ) spectrum in the core level X-ray photoelectron spectra (XPS) further supported the growth of MnFe 2 O 4 (Figure S6B–D).…”
Section: Resultsmentioning
confidence: 99%
“…In both these spectra, the prominent broad absorption band at 1055–1200 cm −1 was assigned to asymmetric vibration of Si–O–Si group 25 , 26 . The peak at 473 cm −1 indicates the bending of O–Si–O with stretching vibrations of silanol groups 27 . The peak at 795 cm −1 was attributed to the bending vibrations of Si–O–Si band 25 .…”
Section: Resultsmentioning
confidence: 99%
“…An important property of MOFs is the huge surface area that can be obtained with the combination of these materials, which has been expanded up to 7,000 m 2 g −1 (Hönicke et al, 2018). The surface area of MOFs is larger than the values reported for other porous materials such as activated carbon or nanomaterials like silica, which ranges from 950 to 2,000 m 2 g −1 (Lu & Xue, 2019) and 1,700 m 2 g −1 (Thahir et al, 2019), respectively, however reported values for adsorption applications usually range below the 1000 m 2 g −1 . Since MOFs are also highly porous, the high amount of available area sites on the surface of the MOFs allows them to adsorb or even catalyze the decomposition of different substances.…”
Section: Water Pollution and The Technological Challenge Of Developin...mentioning
confidence: 99%